Asymptotic Solutions of Fourth Order Near Critically Damped Nonlinear Systems - Rahman, Md. Habibur; Haque, B.M. Ikramul; Akbar, M. Ali (Journal of Informatics and Mathematical Sciences, 2009)
A perturbation technique is developed in this article to solve asymptotic solutions of fourth order near critically damped nonlinear systems based on the Krylov-Bogoliubov-Mitroplskii method. The method is illustrated by an example. The results obtained by the presented technique show excellent coincidence with those obtained by numerical method.